The Impact Of Online Loans On Husbands' Financial Behavior From The Perspective Of Hifz Al-Nafs And Hifz Al- ’Aql - Tomi Apra Santosa; Wisnarni Wisnarni; Widiya Yul; Y. Sonafist; Zufriani Zufriani; Ahmad Zuhdi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
The development of online lending services has provided easy access to financing for the public, but on the other hand, it has also created social, economic, and psychological problems in family life. In the household context, the husband's involvement in online lending can affect financial behavior, decision-making patterns, income stability, and relationships with family members. This phenomenon is important to study from the perspective of maqāṣid al-syarī‘ah, especially the aspects of hifz al-nafs (protection of the soul) and hifz al-‘aql (protection of the mind) because uncontrolled online lending practices can cause mental stress, anxiety, family conflict, and irrational financial decisions. This study uses a qualitative approach with a descriptive study design. Data were collected through in-depth interviews, observations, and documentation of informants who have direct experience or are relevant to the use of online loans in household life. The informant selection technique was carried out purposively by considering the husband's involvement in online lending and its impact on family financial behavior. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing, then interpreted using the hifz al-nafs and hifz al-‘aql perspectives. The results of the study indicate that online loans have an impact on changes in husbands' financial behavior, such as increased consumer tendencies, weak financial planning, dependence on short-term debt, and reduced openness in family financial management. In addition, pressure due to debt collection, high interest rates, and the inability to pay installments cause psychological disorders, household conflicts, and a decrease in the quality of decision-making. From the hifz al-nafs perspective, these impacts indicate a threat to peace of mind, emotional security, and the sustainability of family life. Meanwhile, from the hifz al-‘aql perspective, unwise use of online loans can weaken the husband's rationality, prudence, and ability to make beneficial financial decisions.